SIBAD; Sistem Informasi Akuntansi Berbasis Database Solusi Pembukuan untuk Toko Beras - Endrawati; Aulia Fitri; Firman Surya; Syafira Ramadhea Jr (Politeknik Negeri Padang, 2022)
This study aims to design a computer-based accounting information system and a database application-based accounting information system (SIBAD) using Microsoft Access 2016, which will make it easier to optimize work and minimize errors that occur such as data loss at the Lisa/Emi Rice Shop. The method used in collecting data in this research is interviews with company owners, observing inventory in the warehouse and studying the data provided by company owners, and document review. The data analysis method of this research uses quantitative and qualitative methods. The design of SIBAD using Microsoft Access 2016 starts from the design of the input process output. The design made consists of the company data input menu, beginning balance input, transaction input, and financial reports. The accounting information system that runs at the Lisa/Emi Rice Shop includes a purchase accounting system, a sales accounting system, a cash receipts accounting system, a cash disbursement accounting system for debt payments, and a cash disbursement accounting system for operational costs.